Assessing China's energy conservation and carbon intensity: how will the future differ from the past? - ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2010)
As an important step towards building a 'harmonious society' through 'scientific development', China has incorporated for the first time in its five-year economic plan an energy input indicator as a constraint. While it achieved a quadrupling of its GDP while cutting its energy intensity by about three quarters between 1980 and 2000, China has had limited success in achieving its own 20% energy-saving goal set for 2010 to date. Despite this great challenge at home, just prior to the Copenhagen climate summit, China pledged to cut its carbon intensity by 40-45% by 2020 relative its 2005 levels to help to reach an international climate change agreement at Copenhagen or beyond. This raises the issue of whether such a pledge is ambitious or just represents business as usual. To put China's climate pledge into perspective, this paper examines whether this proposed carbon intensity goal for 2020 is as challenging as the energy-saving goals set in the current 11th five-year economic blueprint, to what extent it drives China's emissions below its projected baseline levels, and whether China will fulfill its part of a coordinated global commitment to stabilize the concentration of greenhouse gas emissions in the atmosphere at the desirable level. Given that China's pledge is in the form of carbon intensity, the paper shows that GDP figures are even more crucial to the impacts on the energy or carbon intensity than are energy consumption and emissions data by examining the revisions of China's GDP figures and energy consumption in recent years. Moreover, the paper emphasizes that China's proposed carbon intensity target not only needs to be seen as ambitious, but more importantly it needs to be credible. Given that China has shifted control over resources and decision making to local governments as the result of the economic reforms during the past three decades, the paper argues the need to carefully examine those objective and subjective factors that lead to the lack of local official's cooperation on the environment, and concludes that their cooperation, and strict implementation and coordination of the policies and measures enacted are of paramount importance to meeting China's existing energy-saving goal in 2010, its proposed carbon intensity target in 2020 and whatever climate commitments beyond 2020 that China may take.
Keywords: Q42; Q43; Q48; Q52; Q53; Q54; Q58; 330; Energy Saving; Renewable Energy; Carbon Intensity; Post-Copenhagen Climate Negotiations; Climate Commitments; China